MORPHOLOGICAL AND ANATOMICAL STUDY OF GALANTHUS WORONOWII LOZINSK. FROM AMARYLLIDACEAE JAUME ST-HIL. FAMILY - F. K. Serebryanaya; K. I. Shestakova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
We have carried out morphological and anatomical studies of Galanthus woronowii L., we have revealed diagnosis indices of lamina, stem, bulb and root. The leaf is hypostomal, dorsoventral, stomatal apparatus of paracytic and anisocytic type. The stem has a fascicular structure, with aerenchyma. The root has primary structure, with tetrarch conductive system. The bulb has a fascicular structure of conductive system with characteristic parenchimal sheath of conductive fascicles